Seed treatment affected establishment and yield in two pennycress lines - Koirala, Nasib; Barker, David J.; Gesch, Russ W.; Mohammed, Yesuf Assen; Heller, Nicholas J.; Hard, Alexander W.; Wells, Samantha S.; Phippen, Winthrop B.; Tas, Pamela; Lindsey, Alexander J. (Frontiers in Agronomy, 2023)
Introduction Oilseed pennycress (Thlaspi arvense L.) is an emerging biofuel crop for use in the aviation industry that has potential as a rotational crop in corn (Zea mays L.)–soybean [Glycine max (L.) Merr.] cropping sequences. Ensuring autumn emergence of pennycress after early broadcast seeding is key because this practice may result in uneven spatial distribution due to the small seed size and variable germination, soil contact, and moisture availability. The objective of this research was to evaluate the impact of five seed treatments and enhancements on autumn establishment in two pennycress lines (MN106NS and tt8-t/ARV1) in broadcast seeding compared with no treatment. Methods Tested treatments were (i) gibberellic acid (GA) soak, (ii) fludioxonil fungicide, (iii) pelleting with diatomaceous earth and a commercial binder, (iv) fungicide plus pelleting, or (v) fungicide plus pelleting with GA added to the binder. Seeds were planted at nine sites in four U.S. states to assess establishment (stand counts and percentage canopy cover) in the autumn and spring and seed yield after maturity. Results The MN106NS line had greater plants m−2 and percent green cover with treatments that included GA compared to the control. Line tt8-t/ARV1 had reduced stands when pelleted compared to the untreated, and establishment was unchanged when treated with GA compared to the untreated. Pelleting treatments without GA were not beneficial for stand establishment of either line. Seed yield for MN106NS was 20% greater than the untreated when treated with GA only or pelleted. Seed yield for tt8-t/ARV1 did not increase over the untreated with any treatment and was reduced by 20%–40% when pelleted. Discussion These results suggest minimal benefit of seed treatment and pelleting for the tested lines under broadcast seeding, though black-seeded lines may still benefit from GA treatment. Plant establishment and yield were negatively correlated with total precipitation post-planting, suggesting that excessive rainfall post-planting (>60 mm) may impede establishment when broadcast seeded.